CORRECTION OF VEGETATIVE DISORDERS IN PARKINSON'S DISEASE AND PARKINSONISM (Academicia Globe: Inderscience Research, 2023)
According to data over the past decades, non-motor symptoms of Parkinson's disease (PD) have attracted special attention of scientists, among which autonomic disorders occupy an important place. According to various sources, the frequency of autonomic disorders in PD reaches 70% - 100%. The structure of autonomic disorders in PD is mainly composed of: cardiovascular disorders (20-63%), gastrointestinal disorders (20-97%), 92%), trophic skin disorders (20-34%), thermoregulation disorders (10-50%).